Regulatory inspection and the changing legitimacy of health and safety. Issue 1 (8th August 2017) - Almond, Paul; Esbester, Mike
Abstract: The regulation of conduct via law is a key mechanism through which broader social meanings are negotiated and expressed. The use of regulatory tools to bring about desired outcomes reflects existing social and political understandings of institutional legitimacy, the meanings attached to regulation, and the values it seeks to advance. But these contextual understandings are not static, and their evolution poses challenges for regulators, particularly when they reflect political framing processes. This paper shows how inspection has been reshaped as a tool within the United Kingdom's health and safety system by changes in the meanings attached to the concept of "risk‐based regulation." While rates of inspection have fallen dramatically in recent years, the nature and quality of inspection have also been fundamentally reshaped via an increasingly procedural and economically rational "risk‐based" policy context. This has had consequences for the transformative and symbolic value of inspection as a tool of regulatory practice.